(untitled) (Journal of actual problems of jurisprudence, 2018)
Today the legal regulation of individual labour disputes is one of the most topical issues in the Republic of Kazakhstan. This article is devoted to establishment of chronological sequence of development of the labour legislation in general, and institute of individual labour disputes, in particular, is the objective requirement of time. Key words: labour disputes, individual labour disputes, history of labour legislation, employee, employer.